Investigating the effect of oral synbiotic on enteral feeding tolerance in critically ill patients: A double‐blinded controlled clinical trial of gut microbiota. (9th July 2022) - Dehghani, Mohammad Hossein; Saghafi, Fatemeh; Bordbari, Zeinab; Zare‐Kamali, Javad; Jafari‐Nedooshan, Jamal; Sahebnasagh, Adeleh
Abstract: Background: Probiotics are beneficial live microorganisms that can modify the gut microbiota. It is assumed that they help improve enteral feeding intolerance (EFI) and nosocomial infections in critically ill patients. The present clinical trial aimed to investigate the efficacy of synbiotics in improving EFI and oropharyngeal aspiration in patients admitted to the intensive care unit (ICU). Methods: This randomized clinical trial was conducted on 105 critically ill patients admitted to the ICU of a tertiary referral hospital affiliated with a medical university. The patients were randomly assigned to either a synbiotic or control group and underwent 7 days of investigation. The primary end point was reduced gastric residual volume, which is suggestive of an improvement in EFI. The secondary end point included requirement for prokinetics, frequency of aspiration, duration of mechanical ventilation, length of ICU stay, and level of consciousness. Results: The present clinical trial showed that synbiotic intervention has resulted in a significantly diminished requirement for prokinetics ( P  = 0.019), fewer oropharyngeal aspirations ( P  = 0.01), improved volume of bolus administration, and decreased gastric residual volume during the 7‐day follow‐up period. The patients who received synbiotic had an improved level of consciousness ( P  = 0.01). Conclusion: This clinical trial showed that the prescription of synbiotic from the initial days of enteral feeding has resulted in a significantly diminished requirement for prokinetics, less oropharyngeal aspiration, decreased gastric residual volume, improved volume of bolus administration, and hence, better tolerance of enteral feeding.